PENGARUH PERMAINAN DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 - AULINA, CHOIRUN NISAK (PPs UNJ, 2012)
The objectives of this research is to find out the effect of the games and mastery of the vocabulary of beginning reading ability of children aged 5-6 years. The games are scrabble and card game while mastery of vocabulary are consist of high mastery of vocabulary and low mastery of vocabulary. The results showed that (1) there are differences in beginning reading ability between children who are given scrabble game and card game, (2) there is an interaction effect between the game and mastery of vocabulary toward beginning reading ability (3) children with higher mastery of vocabulary that are given treatment by scrabble game would have higher beginning reading ability than the treatment given to the child with card game, (4) children with lower mastery of vocabulary that are given treatment by card game would have relatively the same beginning reading ability whether in card game or scrabble game.Keywords: games, mastery of the vocabulary, beginning reading ability